Digital Domination: How LPP TVRI Bali Can Leverage Digital TV to Skyrocket Audience Engagement - Wulandari, Ajeng Ayu; Purnamayanti , Putu Angel (COMMUSTY Journal of Communication Studies and Society, 2023)
The development of information technology is changing the way consumers consume media content. Online-based services can be a threat and opportunity for conventional media players, including television media. To attract the attention of viewers, television broadcast media needs to have a marketing communications strategy that suits the needs of viewers. TVRI Bali as a public broadcasting institution focuses on local cultural broadcast programs and educational information programs, as well as being neutral amidst the speed of information dissemination. This research aims to identify the strategies carried out by TVRI Bali to increase its audience on digital television. This research uses Integrated Marketing Communication (IMC) theory and the concept of segmentation. Researchers use qualitative methods. Data was obtained through observation, interviews and documentation studies. The results of this research, TVRI Bali carries out integrated marketing communications activities to promote its event programs by implementing advertising, direct marketing, internet marketing. sales promotion, public relations, and personal selling to capture and maintain the audience market. TVRI Bali audience segmentation is carried out based on demographic, geographic and psychographic segmentation.